CYP51A polymorphisms of Aspergillus fumigatus in lung transplant recipients: Prevalence, correlation with phenotype, and impact on outcomes. (8th January 2021) - Henry, Benoît; Guenette, Alexis; Cheema, Faiqa; Pérez-Cortés, Armelle; McTaggart, Lisa; Mazzulli, Tony; Singer, Lianne; Keshavjee, Shaf; Kus, Julianne V; Husain, Shahid
Abstract: Azole resistance in Aspergillus fumigatus is increasing worldwide and can affect prognosis. It is mostly mediated by cytochrome P51 (CYP51) mutations. In lung transplant recipients (LTR), little is known regarding the prevalence and clinical impact of CYP51 mutations. One hundred thirty-one consecutive A. fumigatus isolates from 103 patients were subjected to CYP51A genotyping through PCR and sequencing. Antifungal susceptibility testing was performed using the Sensititre YeastOne YO-9 © broth microdilution technique. Correlations between genotype, phenotype, clinical manifestations of Aspergillus infection, and clinical outcomes were made. Thirty-four (26%) isolates harbored mutations of CYP51A; N248K (n = 14) and A9T (n = 12) were the most frequent. Three isolates displayed multiple point mutations. No significant influences of mutational status were identified regarding azole MICs, the clinical presentation of Aspergillus disease, 1-year all-cause mortality, and clinical outcomes of invasive forms. In the specific context of lung transplant recipients, non-hotspot CYP51A-mutated isolates are regularly encountered; this does not result in major clinical consequences or therapeutic challenges. Lay Summary: In 131 isolates of Aspergillus fumigatus isolates originating from 103 lung transplant recipients, the CYP51A polymorphism rate was 26%, mostly represented by N248K and A9T mutations. These mutations, however, did not significantly impact azoles minimal inhibitory concentrations or clinical outcomes.